Twenty articles in didactics of mathematics by Pranas Mašiotas - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2008)
For many years, Pranas Mašiotas (1863–1940) was engaged as a teacher of mathematics, a director of gymnasium and a vice-minister of education. He compiled a number of mathematical manuals for Lithuanian primary and secondary schools. In twenty articles in mathematical didactics, published in the 30s of the 20th century, P. Mašiotas discussed upon the didactic issued that were most topical for teachers of mathematics in the said period.
Keywords: teachers of mathematics; primary school; secondary school; manuals; didactics in mathematics; articles